Managing corporate legitimacy : a toolkit - Baumann-Pauly, Dorothée (Greenleaf Publishing, 2013)
This book develops tools for assessing corporate citizenship (CC), the concept that describes the political role of corporations in global governance. Building on theories in political science, corporate citizenship establishes a new role for the corporation in the global economy. The failure of many governments to provide basic rights for their citizens has given rise to the expectation that globally operating corporations should step in and fill governance gaps, for example in the area of human rights. Today, many large multinational corporations claim to conduct business in a socially responsible manner, yet no tools exist to assess whether and to what degree they have indeed systematically revised their business practices to take on these new responsibilities. Managing Corporate Legitimacy addresses these research gaps by clarifying the role of the corporation as a private actor in global governance at conceptual and empirical levels; by contributing to our theoretical understanding of CC as a new phenomenon in globalization; and by furthering the development of appropriate approaches to CC in practice through its toolkit. The tools developed in this book provide practical and detailed guidance for implementing and embedding CC and managing corporate legitimacy. It will be essential reading for practitioners looking for ways to legitimize their engagement with societal issues and for academics considering how we can better measure the engagement of business with CC.